2021
DOI: 10.12965/jer.2142106.053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical-cognitive training on physical and psychological functions among older adults with type 2 diabetes and balance impairment: a randomized controlled trial

Abstract: Risks of falls among older adults are multifactorial in nature. A combined training program might be beneficial on fall-related outcomes. This study aimed to explore the effects of group-based physical-cognitive trainings on physical and psychological outcomes among older adults with type 2 diabetes mellitus (T2DM) and balance impairment. Fall incidence were also determined. Thirty-seven older adults with T2DM and balance impairment were randomly assigned to control and intervention groups. The intervention pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…The findings were in accordance with the work by Saetae et al, (2018) that found that Qi Gong and Yoga could have a positive impact on health, making the person physically and mentally healthy. Consistent with the study balance and resistance training could reduce risk factor of fall by improving balance and lower limb strength among old adults with T2DM and balance impairment including effectiveness of band exercise in improving muscle strength (Kraiwong et al, 2021;. The finding was also supported by the research of Thaiprasert et al (2019) which found that yoga practice made the elderly healthier physically, mentally and socially.…”
Section: Table 2 Research Resultssupporting
confidence: 81%
“…The findings were in accordance with the work by Saetae et al, (2018) that found that Qi Gong and Yoga could have a positive impact on health, making the person physically and mentally healthy. Consistent with the study balance and resistance training could reduce risk factor of fall by improving balance and lower limb strength among old adults with T2DM and balance impairment including effectiveness of band exercise in improving muscle strength (Kraiwong et al, 2021;. The finding was also supported by the research of Thaiprasert et al (2019) which found that yoga practice made the elderly healthier physically, mentally and socially.…”
Section: Table 2 Research Resultssupporting
confidence: 81%
“…Out of 18 studies, 17 reported post treatment results while only one study reported results at one-year follow up (Vucic Lovrencic et al, 2015). Of the included studies, 10 reported effects of physical activity on glycaemic control (Aylin et al, 2009, De Groot et al, 2019b, Duruturk and Ozkoslu, 2019, Kempf and Martin, 2013, Piette et al, 2011, Putiri et al, 2012, Schneider et al, 2016, Vucic Lovrencic et al, 2015, Yucel and Uysal, 2016, Kraiwong et al, 2021. All these 10 studies used HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies used a physical activity intervention alone. Of the remaining 5 studies, 2 combined physical activity with cognitive behavioural therapy (CBT) (Piette et al, 2011;De Groot et al, 2019b), one study combined it with behavioural activation (Schneider et al, 2016), one study combined it with dietary measures (Osama and Shehab, 2015), while one study combined physical activity with cognitive training (Kraiwong et al, 2021). Eleven studies used aerobic exercises as an intervention, 2 studies used resistance exercises (Lincoln et al, 2011;Putiri et al, 2012) while 5 studies used mixed types of exercises as the intervention (Martinez-Velilla et al, 2021;Kraiwong et al, 2021;Duruturk and Ozkoslu, 2019;Vucic Lovrencic et al, 2015;Aylin et al, 2009).…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations